1998
DOI: 10.1016/s0925-8388(98)00557-x
|View full text |Cite
|
Sign up to set email alerts
|

EPR and optical investigation of europium doped Ba2Mg3F10

Abstract: A recent investigation of the (BaF -MgF ) phase diagram produced several new compounds which are suitable hosts for Rare Earth of each of them to a specific barium lattice site. The luminescence emission of both the 4f -4f 5d and the 4f -4f transitions is observed.6 8The relative importance of the two emissions is strongly temperature dependent. The emission intensities of the intra f-shell P → S 7 / 2 7 / 2 6 transitions increase strongly on going from 295 K to 77 K. Thus, the lowest levels of the 4f 5d confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…The analysis of the EPR and ENDOR spectra was performed as described, for instance, in Ref. 13. Optical-absorption measurements were realized on a Cary 2300 instrument or on a modified Unicam SP800 ͑200-800 nm͒ instrument.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the EPR and ENDOR spectra was performed as described, for instance, in Ref. 13. Optical-absorption measurements were realized on a Cary 2300 instrument or on a modified Unicam SP800 ͑200-800 nm͒ instrument.…”
Section: Methodsmentioning
confidence: 99%
“…[2] can be seen in the emission spectra of Ba 6 Mg 11 F 34 . However, these spectra are clearly distinguishable from those of Eu 2þ doped Ba 2 Mg 3 F 10 [7].…”
Section: Single Crystal Xrdmentioning
confidence: 85%
“…Several phases of the BaF 2 -MgF 2 system have also been doped with rare earth elements and their luminescence properties have been studied to find new lamp phosphors or luminescent thin layer materials for coatings [3][4][5][6][7]. The reasons for the bright emission observed for these compounds are the non-centrosymmetric Ba sites which are occupied by the rare earth ions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 presents the Ba 2 Mg 3 F 10 crystal structure; there are two different Ba 2+ sites and both have C s (m) site symmetry. A previous electron paramagnetic resonance (EPR) investigation of europium doped Ba 2 Mg 3 F 10 single crystals has shown that the Eu 2+ impurity occupies both barium lattice sites [13]. In this paper we present luminescence data for Eu 2+ ions in the Ba 2 Mg 3 F 10 host.…”
Section: The Inter-configurational 4fmentioning
confidence: 87%